Shared medical appointments for patients with a nondiabetic physical chronic illness: A systematic review. (March 2019) - Kelly, F; Liska, C; Morash, R; Hu, J; Carroll, SL; Shorr, R; Dent, S; Stacey, D
Objectives: Shared medical appointments are group appointments, with an optional individual consultation, for patients diagnosed with chronic illnesses. Shared medical appointments improve diabetes management, but little is known about their use for other illnesses. The objective was to determine the effect that shared medical appointments have on patients with a physical chronic illness, healthcare providers, and the healthcare system. Methods: A systematic review was conducted searching databases from January 1970 to September 2016. Eligible trials evaluated shared medical appointments for patients with a homogeneous chronic illness, excluding diabetes and mental illness. Screening, data extraction, and risk of bias were conducted independently by two authors. Analysis was descriptive. Results: Of 2364 citations, nine randomized trials were included. Shared medical appointments were evaluated for cardiovascular illnesses (four studies), breast cancer, chronic kidney disease, Parkinson's disease, stress urinary incontinence, and carpal tunnel syndrome. Compared to usual care, no negative effects on patient quality of life, knowledge and satisfaction were reported. One study reported no difference in healthcare provider satisfaction. Another study showed fewer hospital admissions for patients who attended shared medical appointments. Discussion: Few rigorous studies evaluated the use of shared medical appointments for chronic illnesses. Overall, there appears to be no patient harms. Further studies should include more objective outcomes and larger sample sizes.